Theoretical Foundations of Managing Innovative Processes in Enterprises under Green Economy Conditions (KIUT Publication, 2025)
This article analyzes the theoretical foundations of managing innovative processes in enterprises under the conditions of a green economy. Advanced approaches to effectively organizing innovative activities, enhancing competitiveness, and implementing technological innovations in practice are examined. Based on the research findings, recommendations are developed for optimizing innovative processes in enterprises.